pull down to refresh
(a, b, c) = (x - d, x, x + d)
x
d
(x - d) + x + (x + d) = 3x.
(x - d) \cdot x \cdot (x + d) = x \cdot (x^2 - d^2).
3x = x(x^2 - d^2).
x \neq 0
3 = x^2 - d^2.
x^2 = d^2 + 3.
x = \sqrt{d^2 + 3}
d^2 + 3
d = 1
x^2 = 1^2 + 3 = 4 \quad \Rightarrow \quad x = 2.
x^2
d > 1
(a, b, c) = (x - d, x, x + d)
for somex
andd
. The sum and product of the triplet are:x \neq 0
, divide both sides byx
:x = \sqrt{d^2 + 3}
. Forx
to be a natural number,d^2 + 3
must be a perfect square.d = 1
: The triplet is (x - d, x, x + d) = (1, 2, 3).d
yield a perfect square forx^2
, becaused^2 + 3
is not a perfect square ford > 1
.